Soil carbon stock in the ligth of climate change simulated with the Century model - Oliveira, Janio Gloria; Gravina, Geraldo Amaral; Sousa, Elias Fernandes (Coffee Science - ISSN 1984-3909, 2014)
One of the most important factors in agricultural production is soil quality, which can be evaluated from a physical, chemical and biological set and Carbon (C) is one of the elements that can be used as indicators of the effect of the organic matter cycle in soil-plant system. The Century is a simulation model that, in the long run, analyzes the dynamics of soil organic matter and nutrients in the soil-plant system in several agroecosystems. For the sustainability of coffee production in the southern state of Espírito Santo, this study aimed to simulate, using the Century model, the impact of conilon coffee’s growing on C stocks in the southern region of Espirito Santo’s soil. Based on the IPCC forecast was estimated the impact of rising temperatures in the region on C stocks in the soil. The study was conducted in an experimental area of the Federal Institute of Espirito Santo (Ifes), Alegre. The simulation of the dynamics of organic matter and nutrients was performed using the Century model. It was used climate, management, fertilization and production data of the studied area. There was a significant change in C stocks, with the increase and the decrease of the average temperature, showing variation of 3.7% and 2.7% in the C stock.